Dismissals for Cause: The Difference That Just Eight Paragraphs Can Make - Martins, Pedro S. (Journal of Labor Economics, 2009)
This article presents evidence about the effects of dismissals‐for‐cause requirements, a specific component of employment protection legislation that has received little attention. I study a quasi‐experiment generated by a law introduced in Portugal: out of the 12 paragraphs in the law that dictated the costly procedure required for dismissals for cause, eight did not apply to small firms. Using matched employer‐employee longitudinal data and difference‐in‐differences methods, I examine the impact of that differentiated change in firing costs upon several variables. The results do not indicate robust effects on job or worker flows, although some estimates suggest an increase in hirings. However, firms that gain flexibility in their dismissals exhibit sizable increases in their relative performance. This finding suggests that reducing firing costs of the type studied here increases workers’ effort.